Methodology for measuring the affordability of nutritious foods and diets helps decisionmakers across the globe understand how to better utilize agriculture to improve nutrition - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
A4NH research on the affordability of nutritious foods and diets has led to to recommendations on how countries can better utilize agriculture to improve nutrition and has started to influence donors looking to make key changes to the global food system. IN addition, efforts have increased the capacity of governments and development agencies to use accurate, updated metrics to monitor diet costs and affordability to inform agricultural and food systems interventions.